Anatomical and macromorphological data support a new species of Phyllanthus (Phyllanthaceae) from Southeastern Brazil - Torres, Alícia Marques; Da Silva, Marcos José (Phytotaxa, 2023)
Phyllanthus megastylus, a new species endemic from Southeastern Brazil, is described here based on anatomical and macromorphological data. It is known so far from the state of Espírito Santo and is morphologically similar to P. itamarajuensis, but differs by its densely papillose branches, pink pistillate flowers, disk pistillate with undulate margin and punctiform stigmas. We provide illustrations, preliminary conservation status, phenological data and images taken in habitat. In addition, the new species it is compared anatomically with similar species and its systematic positioning is discussed.